1997
DOI: 10.1023/a:1016942504084
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We examined spectral components of beat to beat variability in AC and DC signals of the reflectance photoplethysmograph at finger and earlobe sites in 20 resting volunteers and 20 patients during propofol, alfentanil, isoflurane, nitrous oxide anaesthesia. We observed that at rest, the majority of spectral power at both sites and in both signals was in the low 'thermoregulatory' frequency band (0.01-0.08 Hz). These fluctuations were greater in the finger than in the earlobe and in the AC signal compared to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Vasoconstriction in a heat-loss effector organ is a typical thermoregulatory response mediated by the sympathetic nervous system during endotoxin challenge (Blessing 2004, Ohashi and Saigusa 1997, Saigusa 1990). Similar to the toe PPGV, the rise in ear PPGV LF and MF powers coincided with the occurrence of ear vasoconstriction, which again confirmed the link between sympathetic vasomotor activity and spontaneous slow waves in PPGV (Bernardi et al 1996, Larsen et al 1997, Nitzan et al 1998, Middleton et al 2008, Tang et al 2010, Javed et al 2010. It is noteworthy that the LF and MF powers in PPGV were actually augmented during the occurrence of vasoconstriction, but not after the vasoconstriction became sustained, meaning that the PPGV spectral powers might be a better indicator of the dynamic change in sympathetic tone, rather than its mean level.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Vasoconstriction in a heat-loss effector organ is a typical thermoregulatory response mediated by the sympathetic nervous system during endotoxin challenge (Blessing 2004, Ohashi and Saigusa 1997, Saigusa 1990). Similar to the toe PPGV, the rise in ear PPGV LF and MF powers coincided with the occurrence of ear vasoconstriction, which again confirmed the link between sympathetic vasomotor activity and spontaneous slow waves in PPGV (Bernardi et al 1996, Larsen et al 1997, Nitzan et al 1998, Middleton et al 2008, Tang et al 2010, Javed et al 2010. It is noteworthy that the LF and MF powers in PPGV were actually augmented during the occurrence of vasoconstriction, but not after the vasoconstriction became sustained, meaning that the PPGV spectral powers might be a better indicator of the dynamic change in sympathetic tone, rather than its mean level.…”
Section: Discussionsupporting
confidence: 63%
“…The average response curves showed that this sudden rise in spectral powers coincided with a fall in toe pulse amplitude, indicating peripheral vasoconstriction (Allen 2007, Avolio 2002, and the transient rise and fall pattern mirrored the change in SBP and DBP. Concurrent changes in the BP and toe PPG signals are best explained by a sudden surge in sympathetic vasoconstrictor drive prior to endotoxic shock, as non-respiratory slow waves in PPGV have been associated with peripheral sympathetic vasomotor activities (Bernardi et al 1996, Larsen et al 1997, Nitzan et al 1998, Middleton et al 2008, Tang et al 2010, Javed et al 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respiration-induced change is one of representative factors that can change IBIs. Respiration could change the intra-thoracic pressure, thus causing blood flow variations in the venous circulation [21] as well as in the arterial system [22]. For example, inspiration can decrease the intra-thoracic pressure, thus reducing the left ventricular stroke volume as well as the pressure and cross-section of the thoracic aorta [23].…”
Section: Discussionmentioning
confidence: 99%
“…The sympathetic control of peripheral vasculature may be monitored by analysing the variability of the finger volume pulse signal measured by the photoplethysmographic (PPG) technique (Bernardi et al 1996, Khanokh et al 2004, Larsen et al 1997, Middleton et al 2008, Nitzan et al 1998. Similar to HRV, the frequency spectrum of finger PPG waveform variability (PPGV) may be divided into LF and HF bands, but the physiologic interpretation of PPGV is different from that of HRV.…”
Section: Introductionmentioning
confidence: 99%